Evaluation of tracheostomy suctioning procedure among nursing and respiratory therapy students: wearable manikin vs. standard manikin - Lumowa, Kevin; Lui, Kin Long; Daher, Noha; Baek, Caroline; Tan, Laren D.; Alismail, Abdullah (Frontiers in Medicine, 2023)
Introduction: This study aims to evaluate cognitive load (CL), emotional levels (EL), and stress levels (SL) of students when using a wearable manikin versus a standard manikin for tracheostomy suctioning (TS).This study was approved by the Institutional Review Board. Subjects were recruited by email. Subjects completed a baseline demographics questionnaire, then they were randomized into two groups: wearable manikin group (WMG) or standard manikin group (SMG). For the WMG, an actor simulated a patient by wearing the device. In phase I, both groups were educated on how to perform TS by video and offered hands-on practice. Then I put through a tracheostomy suctioning clinical simulation and completed a post sim-survey. In phase II, the same survey was repeated after encountering a real patient as part of their clinical rotation.Result: A total of 30 subjects with a mean age 26.0±5.5 years participated. Twenty (66.7%) were respiratory care students and ten (33.3%) were nursing students. In the WMG, the median stress level dropped significantly post phase II compared to post phase I (2(1,4) vs.3(1,5), p=0.04). There were no significant changes in median CL, confidence, and satisfaction levels between post phase II and post phase I (p>0.05). In the SMG, the satisfaction level increased significantly post phase II compared to post phase I (5(4,5) vs.4(2,5), p=0.004), but there were no significant changes in CL, SL, and confidence levels between post phase I and phase II. There was no significant difference in mean EL scores over time and these changes did not differ by group. Subjects in the WMG showed a higher mean competency score than those in the SMG (85.5±13.6 vs. 78.5±20.8, p=0.14, Cohen's d=0.4), yet not significant. Conclusion: Our results showed that the WMG is beneficial in helping bridge the gap of learning TS from the sim setting to the real-world clinical setting. More studies with higher sample size and use of other CL scales that assesses the different types of CL are needed to validate our findings.